2005
DOI: 10.1182/blood-2005-03-1036
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity detection of BCR-ABL kinase domain mutations in imatinib-naive patients: correlation with clonal cytogenetic evolution but not response to therapy

Abstract: Mutations in the kinase domain (KD) of BCR-ABL are the leading cause of acquired imatinib resistance. In some cases, identical mutations were detected at relapse and in pretherapeutic specimens, consistent with selection of resistant clones in the presence of drug. However, the incidence of KD mutations in imatinibnaive patients, irrespective of response to therapy, is unknown. We studied mutation frequency in 66 patients with chronic myelogenous leukemia (CML), using cDNA sequencing and allele-specific oligon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
239
0
9

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(258 citation statements)
references
References 32 publications
10
239
0
9
Order By: Relevance
“…Because previous retrospective studies had identified de novo kinase domain (KD) mutations, Willis and colleagues 29,30,34 prospectively assessed the frequency of mutations in imatinibnaive patients with CML, as well as the longer-term clinical significance of these mutations. Utilizing a combination of an allele-specific PCR assay, together with conventional sequencing, mutations were identified in 15 of 66 patients (23%) before therapy, and they were detected in individuals with accelerated and blast phase disease, but not in CP patients.…”
Section: Spotlightmentioning
confidence: 99%
“…Because previous retrospective studies had identified de novo kinase domain (KD) mutations, Willis and colleagues 29,30,34 prospectively assessed the frequency of mutations in imatinibnaive patients with CML, as well as the longer-term clinical significance of these mutations. Utilizing a combination of an allele-specific PCR assay, together with conventional sequencing, mutations were identified in 15 of 66 patients (23%) before therapy, and they were detected in individuals with accelerated and blast phase disease, but not in CP patients.…”
Section: Spotlightmentioning
confidence: 99%
“…For a relatively few CML patients, resistance to imatinib is present before, or develops during treatment. [8][9][10][11] Several strategies are available to treat imatinib-resistant patients, including imatinib dose escalation, dose adjustment based on pharmacokinetic assessments and the use of novel TKIs ( Figure 1, Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Nested PCRs were performed to isolate and sequence a BCR-ABL fragment spanning the kinase domain using (iProof GC 2 Â Master Mix (no. 172-5320, Bio-Rad, Hercules, CA, USA) and published primers (Willis et al, 2005; Supplementary material).…”
Section: Samples From Patientsmentioning
confidence: 99%